Poly L-Lactide Co-Glycolide/β-Tricalcium Phosphate Interference Screw Fixation for Bone-Patellar Tendon Bone Anterior Cruciate Ligament Reconstruction - Barber, F. Alan; Hrnack, Scott A. (The Journal of Knee Surgery, 2013)
The objective of this study was to prospectively evaluate the clinical effectiveness and radiographic response of a poly (l-lactide co-glycolide)/β-tricalcium phosphate (PlLA/PGA/β-TCP) interference screw used in bone-patellar tendon-bone (BPTB) anterior cruciate ligament (ACL) reconstruction. A prospective, consecutive series of 104 patellar tendon bone-tendon-bone ACL reconstructions fixed with PLLA/PGA/β-TCP biocomposite screws were studied. After receiving the approval from the Institutional Review Board, the following data were collected preoperatively from all patients: physical examination, Lysholm score, Cincinnati, and International Knee Documentation Committee (IKDC) activity scores, and standard knee radiographs. In addition to these, follow-up assessments included Lachman and pivot-shift tests, Tegner scores, and KT side-to-side differences. Surgical failure was defined by a 2+ Lachman test, positive pivot-shift test, side-to-side KT difference of greater than 5 mm or subsequent ACL revision surgery. Approximately 95% of patients (99 of 104) with an average follow-up of 36 months (range, 24 to 68) are reported. The average age was 30 years (range, 13 to 57 years). Postoperatively, four patients demonstrated +1 Lachman score and one patient demonstrated a +2 Lachman score. Postoperative pivot-shift tests were a trace positive in one patients and +1 in two patients. The average KT side-to-side difference was 0.65 mm. All, but five patients, demonstrated KT side-to-side measurements of 3 mm or less and those five demonstrated measurements of 5 mm or less. No revision reconstructions were performed. Significant improvements in Cincinnati score (41 to 85 postoperative) and Lysholm score (46 to 90) were observed. The average postoperative Tegner score was 7. IKDC activity score increased from 2.3 to 3.1. Approximately 4% of patients (4 of 99) met the criteria for failure. A PLLA/PGA/β-TCP biocomposite interference fixation screw provides good graft fixation, with good radiographic incorporation, without adverse events.The level of evidence of the study is IV.
Keywords: anterior cruciate ligament; PLLA/PGA screw; interference screw; biocomposite